2017
DOI: 10.1017/s1041610217000655
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychology outcome measures for family caregivers of people living with dementia: a systematic review

Abstract: There are some robust positive measures in existence for family caregivers of people living with dementia. However, lack of reporting of the psychometric properties hindered the quality assessment of some outcome measures identified in this review. Future research should aim to include positive outcome measures in interventional research to facilitate a greater understanding of the positive aspects of caregiving and how these contribute to well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 39 publications
(56 reference statements)
1
65
0
2
Order By: Relevance
“…A recently published review article on positive psychology outcome measures for family caregivers of people living with dementia showed that resilience was one of several outcomes in research in this field. In addition, emerging constructs of self-efficacy, spirituality, rewards, gain and meaning were in line with positive psychology theory (Stansfeld et al, 2017). Along with other mastery theory in the field, this study shows a variety of possible positive outcomes related to the role of family caregiver, which confirms that we must exercise caution in favouring or emphasizing one theory over another.…”
Section: The Role and Influence Of Day Care As A Community Resourcesupporting
confidence: 81%
“…A recently published review article on positive psychology outcome measures for family caregivers of people living with dementia showed that resilience was one of several outcomes in research in this field. In addition, emerging constructs of self-efficacy, spirituality, rewards, gain and meaning were in line with positive psychology theory (Stansfeld et al, 2017). Along with other mastery theory in the field, this study shows a variety of possible positive outcomes related to the role of family caregiver, which confirms that we must exercise caution in favouring or emphasizing one theory over another.…”
Section: The Role and Influence Of Day Care As A Community Resourcesupporting
confidence: 81%
“…Although the existing outcome measures predominately focus on the negative aspects of caregiving, the positive aspects of caring, such as self-efficacy, resilience, rewards, meaning and spirituality, have been overlooked [22]. The positive aspects of caring could aid in the development of relevant positive psychology interventions [23]. Based on the above caregiver health issues, several international agreements and conventions were drafted by the WHO and Alzheimer's Disease International (ADI), and some countries also have policies protecting the rights of caregivers, such as the 10/66 'Helping Carers to Care' train-the-trainer intervention in ADI [24], a national strategy for carers and Care Act in the UK [25][26][27][28], and the national dementia strategies in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Although the existing outcome measures predominately focus on the negative aspects of caregiving, the positive aspects of caring, such as self-efficacy, resilience, rewards, meaning and spirituality, have been overlooked [23]. The positive aspects of caring could aid in the development of relevant positive psychology interventions [24]. Based on the above caregiver health issues, several international agreements and conventions were drafted by the WHO and Alzheimer's Disease International (ADI), and some countries also have policies protecting the rights of caregivers, such as the 10/66 'Helping Carers to Care' train-the-trainer intervention in ADI [25], a national strategy for carers and Care Act in the UK [26][27][28][29], and the national dementia strategies in Australia.…”
Section: Discussionmentioning
confidence: 99%